Acoustic Change Complex as a Neurophysiological Tool to Assess Auditory Discrimination Skill: A Review - Sanju, Himanshu Kumar; Jain, Tushar; Kumar, Prawin (International Archives of Otorhinolaryngology, 2023)
Introduction Acoustic change complex (ACC) is a type of event-related potential evoked in response to subtle change(s) in the continuing stimuli. In the presence of a growing number of investigations on ACC, there is a need to review the various methodologies, findings, clinical utilities, and conclusions of different studies by authors who have studied ACC.Objective The present review article is focused on the literature related to the utility of ACC as a tool to assess the auditory discrimination skill in different populations.Data Synthesis Various database providers, such as Medline, Pubmed, Google, and Google Scholar, were searched for any ACC-related reference. A total of 102 research papers were initially obtained using descriptors such as acoustic change complex, clinical utility of ACC, ACC in children, ACC in cochlear implant users, and ACC in hearing loss. The titles, authors, and year of publication were examined, and the duplicates were eliminated. A total of 31 research papers were found on ACC and were incorporated in the present review. The findings of these 31 articles were reviewed and have been reported in the present article.Conclusion The present review showed the utility of ACC as an objective tool to support various subjective tests in audiology.
Keywords: auditory discrimination; review; acoustics